Proporsi Sari Labu Kuning (Cucurbita moschata) terhadap Karakteristik Yoghurt Layak Konsumsi Ditinjau dari pH dan Uji Organoleptik - Alpina, Lisa; Dharmawibawa, Iwan Doddy; Hajiriah, Titi Laily (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Yogurt is one of the functional foods obtained from fermented milk with the help of Lactic Acid Bacteria (LAB). Several innovations were made to improve the functional properties of yogurt by adding ingredients rich in fiber, one of which is pumpkin. The nutritional content of pumpkin is quite complete, and its utilization is still minimal, so this pumpkin has the potential to be developed as an alternative in making yogurt. The purpose of this study was to determine the effect of the proportion of pumpkin juice on the characteristics of yogurt that is suitable for consumption in terms of pH and organoleptic tests. The research design used was a Randomized Block Design (RAK) using 3 treatments, namely: the first treatment 1:1 (pumpkin: water); second treatment 1:2 (pumpkin: water); and the third treatment 1:3 (pumpkin: water) with 4 replications. The pH test used a pH meter and pH 7 buffer. Based on the results of laboratory tests, the highest pH value was 6.67 in the first treatment (P1), and the lowest pH was 5.62 in the second treatment (P2). For the organoleptic test, the color is yellow to orange, the taste of yogurt obtained is slightly sour to sour, the aroma of pumpkin yogurt is pungent, and the texture is watery to thick.